Green Composite Film Synthesized from Agricultural Waste for Packaging Applications - Dixit S.; Yadav V.L. (My University, 2025)
Plenty available agricultural wastes are getting keen attention as a reinforcing agent in the polymer matrix for researchers due to their readily available, lightweight and low cost. The higher cellulosic characteristic content in agro-waste justified the suitability of this fiber for the fabrication of green packaging film. This chapter enlightened the perfect use of abundantly available agricultural wastes in a reinforcement of the polymer matrix for packaging application. Different kinds of agricultural wastes, i.e., hemp, wheat straw, rice straw, banana, corn, jute, sisal, etc. have been used for various reinforcement applications. Many kinds of literature have also reported some improving interfacial interaction techniques for enhancing the suitability of agro-waste in the matrix. After listing the strategies, various testing methods such as mechanical and thermal stabilities, impact strength, optical characteristics and hydrophobic nature for composites based on agro-waste are presented in this chapter to elucidate the reliable use of lignocellulosic wastes for synthesizing green packaging film. © 2021, Springer Nature Singapore Pte Ltd.